Representing rebellion : visual aspects of counter-insurgency in colonial India - Rycroft, Daniel J. (Oxford University Press, 2006)
Contribution of Santal, South Asian people in the freedom struggle against British rule in India; covers the period, 1845-1856; study based on pictorial representations.